Krytyk i/a recenzent – znaczenie pojęć w słowniku i w tekście - Krauz, Maria (Słowo. Studia językoznawcze, 2021)
The subject of the article is to discuss the evolution of the meaning of terms that are part of the critical discourse: critic and reviewer. The author, analyzing the lexicographic definitions from older and contemporary sources, and the use of the discussed lexemes, collected primarily in the resources of the National Corpus of the Polish Language, looks for answers to the questions of whether critic and reviewer are synonymous terms, how their meaning evolves in dictionaries and in the text, in which new contexts: whether the subject of the review changes, what characteristics the person evaluating someone or something has, and what actions are taken by critics and reviewers.